Association of coffee consumption pattern and metabolic syndrome among middle-aged and older adults: A cross-sectional study - Nina, Ren; Lingling, Huang; Qiushuang, Li; Honglin, Guo; Liyuan, Sun; Yuting, Zhang (Frontiers in Public Health, 2023)
Objectives: The association between coffee consumption and risk of metabolic syndrome (MetS) remains inconsistent. The aim of this study was to evaluate the association between coffee intake and components of MetS. Method: A cross-sectional survey including 1719 adults (53.46 % female) was conducted in Guangdong, China. Data on age, gender, education level, marriage status, BMI, current smoking and drinking status and breakfast habit, coffee consumption type and daily servings were derived based on two-day, 24-hour recall. MetS was assessed according to the International Diabetes Federation definition. Multivariable logistic regression was conducted to examine the association between the coffee consumption type, daily servings and the components of MetS. Results: Regardless of the coffee type, compared with non-coffee consumers, coffee consumers had higher ORs of the elevated FBG in both men (OR 3.590; 95%CI: 2.891, 4.457) and women (OR 3.590; 95%CI: 2.891, 4.457). In women, the risk of elevated BP was 0.553 times (OR: 0.553; 95%CI: 0.372, 0.821, P = 0.004) for people who drank total coffee > 1 serving / day than for non-coffee drinkers. Conclusion: In conclusion, regardless of type, coffee intake was associated with an increased prevalence of fasting blood glucose in both men and women, but has a protective effect hypertension only on women.